2008
DOI: 10.1021/bp060349b
|View full text |Cite
|
Sign up to set email alerts
|

Heterologous GPCR Expression: A Bottleneck to Obtaining Crystal Structures

Abstract: G protein-coupled receptors (GPCRs) are an important, medically relevant class of integral membrane proteins. Laboratories throughout all disciplines of science devote time and energy into developing practical methods for the discovery, isolation, and characterization of these proteins. Since the crystal structure of rhodopsin was solved 6 years ago, the race to determine high-resolution structures of more GPCRs has gained momentum. Since certain GPCRs are currently produced at sufficient levels for X-ray crys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
91
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(92 citation statements)
references
References 103 publications
1
91
0
Order By: Relevance
“…[3][4][5] and suggests that this mutation does influence the activity of CP55,940. This result is consistent with CB 1 K3.28 192 A mutation studies that showed a significant loss of binding affinity and efficacy for the classical cannabinoid, HU-210, the nonclassical cannabinoid, CP55,940, and the endogenous cannabinoid, anandamide (33).…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…[3][4][5] and suggests that this mutation does influence the activity of CP55,940. This result is consistent with CB 1 K3.28 192 A mutation studies that showed a significant loss of binding affinity and efficacy for the classical cannabinoid, HU-210, the nonclassical cannabinoid, CP55,940, and the endogenous cannabinoid, anandamide (33).…”
Section: Resultsmentioning
confidence: 95%
“…4-Cyclohexylbenzaldehyde (2.4 g, 0.0127 mol), ammonium acetate (1.74 g, 0.0226 mol, 1.78 eq), and nitromethane (25 ml) were combined in a round bottom flask, and the reaction mixture was heated at 100°C with stirring under nitrogen for 2.5 h. The brown-orange reaction mixture was allowed to cool at room temperature and concentrated. The resulting oil was dissolved in EtOAc, and the solution was washed with 1 N HCl followed by saturated NaHCO 3 . The organic phase was separated, dried (MgSO 4 ), and filtered, and the filtrate was concentrated to give an orange oil.…”
Section: -Cyclohexyl-4-[(e)-2-nitroethenyl]benzene (3)-mentioning
confidence: 99%
“…Planar lipid rafts and caveolae both influence GPCR signaling by either excluding or recruiting G-proteins and their effectors. Because native GPCRs are not highly expressed in cells (McCusker et al, 2007), lipid rafts concentrate GPCRs and their associated proteins to promote receptor dimerization and signaling. Caveolar-localized GPCRs are also subject to more rapid endocytosis, which represents another way to modulate GPCR signaling (Chini and Parenti, 2004).…”
Section: Gpcr Structure-function Relationshipmentioning
confidence: 99%
“…Many GPCRs, like other membrane proteins, are not easily expressed, however, so deeper penetration into the family will require developments in this area. 55 Although eukaryotic expression systems will continue to be utilized as they can provide a more natural milieu for GPCRs, E. coli seems particularly promising as many GPCRs can already be expressed in their active form in E. coli. 48,[56][57][58][59] Expression of unmodified…”
Section: Expressionmentioning
confidence: 99%